Caput regni barbarorum: Centra władzy królestw barbarzyńskicha rzymska „prowincja” w V– VI wieku (wybrane przykłady: Kartagina i Braga) - Wilczyński, Marek (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
In the 5th century, the centers of domination of the tribal kings stabilized on western Roman territory. The barbarian rulers chose the existing Roman administrative centers as their residences. These cities were the focal points of royal administration, religious and cultural life, and military garrisons. The contacts and interactions between the barbaric “centre”and the Roman (or Romanized) “province” are discussed in this article.
Keywords: centra władzy królów "barbarzyńskich; ludność rzymskiej „prowincji; konflikt i koegzystencja; późny antyk